Rapid progression of type 2 diabetes and related complications in children and young people-A literature review - (:unkn) unknown (WILEY, 2020)
Type 2 diabetes (T2D) is suggested to progress faster in children and young people vs type 1 diabetes (T1D) in the same age group and T2D in adults. We reviewed the evidence base for this. A literature search was performed of PubMed-indexed publications between 2000 and 2018, for the terms pediatric and T2D. Results were combined and filtered for those relating to progression. Searches of abstract books from Latin American and Asian congresses were performed to include these populations. Pediatric populations were defined as <25 completed years of age. Of the articles and congress abstracts found, 30 were deemed relevant. Dividing the studies into categories based on how T2D progresses, we found the following: (a) yearly beta-cell function deterioration was shown to be 20% to 35% in children with T2D compared with 7% to 11% in adults with T2D, despite similar disease durations; (b) retinopathy progression was likely dependent on diabetes duration rather than diabetes type; however, nephropathy, neuropathy and probably hypertension progressed faster in youth-onset T2D vs T1D. Nephropathy progression was similar to adults with T2D, allowing for disease duration. Youth with T2D had a worse cardiovascular (CV) risk profile than youth with T1D, and a faster progression to CV death. (c) Progression to treatment failure was faster in youth-onset T2D vs adult-onset T2D. Substantial evidence exists for faster progression of T2D in pediatric patients vs T1D or adult-onset T2D. New treatments targeting the pathology are needed urgently to address this issue.
Keywords: complications; diabetes; pediatric; progression; BETA-CELL FUNCTION; IMPAIRED GLUCOSE-TOLERANCE; OBESE WHITE-CHILDREN; 5-YEAR FOLLOW-UP; RISK-FACTORS; YOUTH; ADOLESCENTS; RETINOPATHY; MORTALITY; MELLITUS